Optimize Transmission of Image over Integrated Mobile WiMAX and WiLAN Network - More, Anant R.; Vishal A., Wankhede; Prasad, M.S.G. (International Journal of Engineering and Technology, 2018)
The problem of multiuser downlink resource allocation in Mobile WiMAX system was studied. Three different network scenarios considered for the transmission of image data. Resource allocation is done using Active Set Optimization and Genetic Algorithm, for all the three network scenarios. Simulation results show that information fed back and association among subcarriers play vital role to improve system performance. As compared to reduced complexity, resource allocation using Active Set Optimization and Genetic Algorithm seems especially attractive as the number of users increases for Image Data. It is observed through simulation that the System using Genetic Algorithm performs better than Active Set. Linear Resource Allocation in terms of significantly decreasing the computational complexity and achieve higher capacities, while being applicable to a more general class of systems. As Genetic Algorithm follows constraints of Stochastic processes it didn’t give results highest in all Experiment Conducted. It is also observed that for Integer-Binary Objective function Performance of Genetic Algorithm is not that much satisfied because of its stochastic processing. Also processing time required to reach final optimize variables values is too much.